THE RESEARCH OF THE STABILITY OF ADHESIVE JOINTS OF HARD-WOODED SPECIES (OAK WOOD), FORMED BY MODIFIED POLYVINYL-ACETATE (PVA) COMPOSITION, TOWARDS THE INFLUENCE OF WATER AND HIGH TEMPERATURES - Solonynka , Vasyl (Forestry, Forest, Paper and Woodworking Industry, 2012)
The results of the research of adhesive joint strength changes of oak wood formed by adhesives on the basis of PVA dispersion of domestic and foreign production under the influence of cyclic temperature and humidity testing.